On Medical Informatics - Haux, R. (Methods of Information in Medicine, 1989)
This paper summarizes the author’s point of view of defining medical informatics, to stimulate further discussions on how this “newly emerging discipline” should further proceed. We realize that the term “informatics” is related rather to the term “information science” than to “computer science”. Accordingly, medical informatics deals with the systematic processing of information in medicine. Many information systems in medicine are interrelated and can hardly be regarded as independent systems. As a result, medicine becomes gradually more an “empirical science of extreme complexity”. Because of its complexity and wide range of applications, medical informatics should be considered as a separate discipline, its aim being to contribute to the systematic processing of information in medicine. The contribution of medical informatics should be a better understanding of the human being and means for the provision of high quality patient care.
Keywords: Medical Informatics; Information Processing